2022
DOI: 10.3389/fimmu.2022.972345
|View full text |Cite
|
Sign up to set email alerts
|

Research advance of natural products in tumor immunotherapy

Abstract: Cancer immunotherapy has emerged as a novel anti-tumor treatment. Despite significant breakthroughs, cancer immunotherapy remains focused on several types of tumors that are sensitive to the immune system. Therefore, effective strategies to expand its indications and improve its efficacy become key factors for the further development of cancer immunotherapy. In recent decades, the anticancer activities of natural products are reported to have this effect on cancer immunotherapy. And the mechanism is largely at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 88 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…A wide range of traditional medicine and natural products can be considered for therapy against several diseases, including COVID-19 [ 8 , 9 ], cancer [ 10 , 11 ], parasitic infections [ 12 , 13 ], diabetes [ 14 , 15 ], and obesity [ 16 ]. In fact, the WHO recognizes the importance of traditional medicine, especially in underdeveloped countries, where approximately 85% of the population uses medicinal plants as a therapeutic alternative.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of traditional medicine and natural products can be considered for therapy against several diseases, including COVID-19 [ 8 , 9 ], cancer [ 10 , 11 ], parasitic infections [ 12 , 13 ], diabetes [ 14 , 15 ], and obesity [ 16 ]. In fact, the WHO recognizes the importance of traditional medicine, especially in underdeveloped countries, where approximately 85% of the population uses medicinal plants as a therapeutic alternative.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, natural products often serve as lead templates and are subjected to structural optimization to generate clinically useful structures. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, natural products often serve as lead templates and are subjected to structural optimization to generate clinically useful structures. 5,6 Dehydroabietic acid (DHA), the main component of the traditional Chinese medicine rosin, is a naturally occurring tricyclic diterpene aromatic abietane with excellent biocompatibility and biodegradability. 7,8 DHA and its derivatives exhibit a broad range of biological activities, including antimicrobial, 9,10 anti-inflammatory, 11 antioxidant, 12 and vasodilator 13 activity.…”
Section: Introductionmentioning
confidence: 99%
“…For both Schinus species, previous works have shown that non-polar to mid-polar extracts obtained from the different plant parts (Garzoli et al, 2019 ; Mügge et al, 2021 ; Oliveira et al, 2018 ; Ovidi et al, 2021 ) and the essential oil obtained from the leaves (Díaz et al, 2008 ; Garzoli et al, 2019 ; Mahmoud et al, 2011 ; Santana et al, 2012 ) or fruits (Aboalhaija et al, 2019 ; Bendaoud et al, 2010 ; Guzzo da Silva et al, 2019 ; Matsuo et al, 2011 ; Oliveira et al, 2018 ) are active against different cancer cell lines. Most cytostatic or cytotoxic compounds used today in cancer treatment are derived from plants (Beutler, 2019 ; Davison & Brimble, 2019 ), but the advances in this field are slow due to the difficulty in applying high-throughput methods, which are useful for screening synthetic molecule libraries, to complex mixtures obtained from plant parts (Beutler, 2019 ; Davison & Brimble, 2019 ; Hackman et al, 2020 ; Huo et al, 2022 ; Mazumder et al, 2018 ; Najmi et al, 2022 ). The application of metabolomics in cancer research comes with many challenges, such as technological limitations, high costs of instrumentation, and data processing, among others (Oyenihi et al, 2021 ), but the introduction of non-targeted hyphenated HPTLC as a supplementary or supporting tool for metabolomic analysis can bring advantages for allowing both a pre-screening of interesting biological activities and direct determination of structure–activity relationship after the elution of active substances from the plate into HRMS or nuclear magnetic resonance (NMR) spectroscopy workflows (Ge et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%